Conceptual Understanding Analysis Through Two-Tier Model Diagnostic Tests on Acid-Base Materials - Sintia Ayu Dewi; Endang Susilaningsih; Triastuti Sulistyaningsih (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2018)
This research aims to organize instrument of computer-based two-tier multiple choices diagnostic test. The research method used was quantitative and qualitative method. This research was conducted in class XI MIPA 3 and XI MIPA 4, Senior High School 1 Ungaran. The research procedure was designed starting from selecting the difficult subjects, arranging test plan, designing two-tier model of diagnostic test, designing web, tryout, analysis of tryout data, diagnostic test, interview, and analysis of concept understanding. The finding of the research that the instrument was valid and reliable. The result of students’ concept understanding of acid-base on implementation class showed that 9 of 35 students (26.86%) understood the concept thoroughly, 4 of 35 students (8.43%) got misconception, 1 of 35 students (3.71%) kept guessing, 12 of 35 students (34.86%) grasped less understanding while 9 of 35 students (26.14%) did not understand the concept of Acid-Base. The inference drawn of this recent study is that computer-based two-tier diagnostic test instrument can be used to analyze students’ concept understanding about acid-base by combined interpretation of students’ answers with several categories of concept understanding, misconception, guessing, less understanding of the concept, and failure to understand the concept.